Efforts to Reduce Employee Deviant Behavior in Islamic Educational Institutions - Fatmah Bagis; Astika Nurul Hidayah; Abid Yanuar Badharudin; Uswatun Hasanah; Mega Aprillia Pratamasari (ITB AAS Indonesia Surakarta, 2024)
This research explores the factors that influence employees' tendencies to engage in deviant behavior in the workplace and contribute to its creation. This research aims to determine the influence of workplace behavior on organizational commitment, spirituality, ethical leadership, organizational justice, and job satisfaction, using a social exchange theory framework. This research uses a sampling method as a non-random sampling method based on samples selected for statistical analysis. The respondents used in this research were 232 employees of the Islamic University of Purwokerto City. The research uses hardfiles and softfiles (Google forms) for data collection. Data collection was carried out using a Likert Scale-based questionnaire and tested using the Smart PLS application. The findings show that although workplace spirituality and organizational commitment have a direct negative impact on workplace deviant behavior, this relationship is not statistically significant. On the other hand, Job Satisfaction and Organizational Justice have a negative but significant effect on conservation behavior in the workplace. Additionally, there is a weak but positive relationship between workplace deviant behavior and ethical leadership. Keywords: Workplace Deviance Behavior, Islamic Instittution, Workplace Spirituality, Ethical Leadership.